Distribution and virulence of Escherichia coli harboring cyclomodulins and supplementary virulence genes isolates from clinical and environmental samples - DeLira-Bustillos, Nora; Angulo-Zamudio, Uriel A.; Leon-Sicairos, Nidia; Flores-Villaseñor, Hector; Velazquez-Roman, Jorge; Tapia-Pastrana, Gabriela; Martínez-Villa, Francisco A.; Velázquez-Cruz, Rafael; Salmerón, Jorge; Canizales-Quinteros, Samuel; Canizalez-Roman, Adrian (Microbial pathogenesis, 2024)
This study aimed to determine the prevalence of cyclomodulins (cdt, cnf, pks and cif) in Escherichia coli (E. coli) isolated from clinical and environmental samples, the presence of supplementary virulence genes (SVG), antibiotic resistance, and in vitro cytotoxicity. 413 E. coli were isolated from clinical (stool from obese subjects, normal weight subjects, children with diarrhea, and children without diarrhea; and urine from pregnant and non-pregnant women with urinary tract infections) and environmental (water and different foods) samples. PCR was performed to identify E. coli pathotypes, the four cyclomodulins, and 18 SVG; virulence score, cytotoxic assay, and antibiotic resistance assay were performed. Fifteen percent of E. coli were positive for cyclomodulins and were found in all isolation sources; however, in children with diarrhea, they were more frequent. The most frequent cyclomodulin was cdt. More DEC strains harbor cyclomodulins than non-DEC, and cyclomodulins were most frequent among aEPEC pathotype. SVG ehaC was associated with cyclomodulin-positive strains. Cyclomodulin-positive E. coli had a higher virulence score but no significant cytotoxic activity. They were slightly more resistant to antibiotics. In conclusion, cyclomodulins-positive E. coli was widely distributed in humans, food, and the environment, and they were associated with SVG ehaC, suggesting that these genes may play a role in the pathogenesis of the cyclomodulins. However, more research is needed. •E. coli isolates from clinical and environmental samples contain cyclomodulins.•The most prevalent cyclomodulin in E. coli was cdt.•DEC strains harbored more cyclomodulins than non-DEC strains.•- SVG ehaC was associated with cyclomodulin-positive strains.•Cyclomodulin-positive E. coli had a higher virulence score and were antibiotic-resistant.